Analysis of the federal, state and local governments responses to environmental issues and management in Nigeria (2015)
Nigeria is blessed with immense natural resources which are spread over her various ecosystems. However, these natural resources have continued to suffer pressures in the quest for development, uncontrolled socio-economic activities and consumption thus putting the land, air, water, forest and animals species to greater risk of abuse and deterioration. To arrest monumental degradation and extinction of these natural resources, Nigeria governments, at each stratum of governance, are constitutionally saddled with responsibilities to ensuring the protection and sustainability of the environment in the face of natural resources exploration and exploitation. This paper seeks to critically analysis the responses of the three tiers of government in Nigeria to environmental problems. The paper will in particular examine the legislative lists as relate to environmental matters under the Constitution of the Federal Republic of Nigeria, 1999 (as amended). The objective of this exercise is to determine the justification or otherwise of the authority given to each tiers of government to legislate on environmental issues. The outcome from this pursuit will be used to proffer solutions to the apparent lopsidedness in the allocation of legislative powers and functions to the three tiers of government in Nigeria on environmental issues.